The potential of oven dry sewage sludge as partial sand replacement in concrete - Mohd Syukran, Ab Razak (2016)
The consumption of natural sand taken from the river was too high due to its excessive use in concrete. The demands for this natural sand were increasing from time to time, especially on developing countries, for instance, Malaysia. Thus, the construction industries are in stress to identify alternative methods and materials to reduce the demand for natural sand. Sewage sludge has been seen as one of the alternative that can replace sand in concrete mixture production and therefore could reduce the excessive production of sewage sludge. It has been reported that Malaysia produce about 3 million m³ of sewage sludge per year and it has been estimated to rise to 7 million m³ in the year of 2020. These situations have contributed to increasing of solid waste generated and have led to environmental issues. This research was ran to study the properties of concrete cube mixture that contained various percentage of sewage sludge that have been sieved as partial sand replacement, which were 0%, 10% and 20%. The size of the specimens that been used were 100x100x100 mm (length x width x height). The specimens subjected to two types of curing method, which were water and air curing for 3, 7 and 28 days period. The specimens then tested for compressive strength test, flexural strength, rebound hammer test and ultrasonic pulse velocity test. The results from these tests shows the suitable percentage of sewage sludge as partial sand replacement and suitable curing method for this concrete mix production.